The C‐terminus of tissue factor pathway inhibitor‐α inhibits factor V activation by protecting the Arg1545 cleavage site. (3rd December 2016) - van Doorn, P.; Rosing, J.; Wielders, S. J.; Hackeng, T. M.; Castoldi, E.
Abstract : Essentials The C‐terminus of tissue factor pathway inhibitor (TFPIα) binds to the B‐domain of factor V (FV). The functional consequences of this interaction were investigated in plasma and model systems. The TFPIα C‐terminus inhibited thrombin generation in plasma, but not in the presence of FVa. The TFPIα C‐terminus inhibited FV activation by preventing cleavage at Arg 1545 . Summary: Background: Factor V (FV) is a carrier and a cofactor of the anticoagulant protein tissue factor pathway inhibitor‐α (TFPIα), whose basic C‐terminus binds to an acidic region in the B‐domain of FV. Proteolysis of FV at Arg 709, Arg 1018 and Arg 1545 by activated FX (FXa) or thrombin removes the B‐domain, and converts FV into a procoagulant cofactor (activated FV [FVa]) of FXa in the prothrombinase complex. However, retention of the acidic region in partially activated FV makes prothrombinase activity susceptible to inhibition by TFPIα. Objective/Methods: To investigate the effect of the TFPIα C‐terminal peptide (TFPIα C‐term) on thrombin generation in plasma and on FV activation in model systems. Results: TFPIα C‐term inhibited tissue factor‐initiated and FXa‐initiated thrombin generation in a dose‐dependent manner. Failure to inhibit thrombin generation in FV‐depleted plasma reconstituted with FVa indicated that the peptide effect was mediated by the acidic region of FV, and was localized at the level of FV activation and/or prothrombinase. In model systems, TFPIα C‐term inhibited both FV activation and prothrombinase activity. Western blot analysis showed that the peptide impaired cleavage at Arg 1545 by both thrombin and FXa. The inhibition was stronger for FV‐short, which binds TFPIα with higher affinity. Similar results were obtained with full‐length TFPIα. Conclusions: Cleavage of FV at Arg 1545, which abolishes the anticoagulant properties of FV and commits FV to the procoagulant pathway, is inhibited by binding of the TFPIα C‐terminus to the FV acidic region. Possible targets of this new anticoagulant function of TFPIα are low‐abundance FV(a) species retaining the acidic region.